Detection of polysaccharides from local algae in fresh water - Al-Rikabi, Nawras; Roa'a Jaafar Khairallah , (University of Thi-Qar Journal of Science, 2025)
-The research focused on identifying the polysaccharide composition of Cladophora algae species collected  from the Tigris River for carrageenan, agar and alginate analysis. The biochemical diversity  of Cladophora green algae was demonstrated through the discovery of compounds traditionally linked to red and brown  marine algae. HPLC analysis provided detailed information about polysaccharide distribution through its measurement of  polysaccharide content.The analysis of Cladophora revealed that carrageenan and agar  existed at 1.21% and 1.25% levels while alginate reached  1.46%. The discovery of carrageenan in green algae contradicts the common belief that this substance  exists only within rhodophyta species. The polysaccharide synthesis and accumulation process in the  Tigris River appears to be influenced by the river's unique freshwater environment together with its low  salinity and fluctuating nutrient levels and seasonal temperature changes. The main polysaccharide identified in the  sample was agar which suggested conserved biosynthetic pathways and alginate presented industrial value despite its minimal  concentration.  The two unknown polysaccharide peaks at positions 3 and 10 played a  crucial role in establishing the biochemical profile of the sample.The research shows how environmental conditions together with  methodological approaches affect polysaccharide production. The minimal amounts of carrageenan, agar and  alginate suggest that Cladophora could serve as a supplementary resource instead of the primary one. The  discovery of different unknown polysaccharides creates new research opportunities for industry to explore potential new compounds.